CTIM-14. COMPREHENSIVE BIOMARKER ANALYSIS OF RESPONDERS AND NON-RESPONDERS IN A PHASE IIA TRIAL OF A CMV VACCINE IMMUNOTHERAPEUTIC CANDIDATE (VBI-1901). (14th November 2022) - Wen, Patrick Y; Reardon, David A; Forst, Deborah; Lee, Eudocia; Daoud, Teresa; Berthoud, Tamara; Soare, Catalina; Diaz-Mitoma, Francisco; Anderson, David E; Lassman, Andrew; Iwamoto, Fabio
Abstract: Cytomegalovirus (CMV) antigens have been reported in over 90% of GBMs. CD4 + and CD8 + T cells are most frequently directed against the gB and pp65 antigens, respectively, which are immunogenic targets in a CMV-based GBM immunotherapeutic. First-recurrent GBM patients were enrolled, with Karnofsky Performance Status of at least 70, to receive VBI-1901 (a gB/pp65 enveloped virus-like particle [eVLP]) adjuvanted with GM-CSF and given intradermally (NCT03382977). Patients were vaccinated with VBI-1901 every 4 weeks, with serologic immune-monitoring 2 weeks after each vaccination and surveillance brain MRI scans every 6 weeks. Sixteen patients (8 women, 8 men) with a median age of 55 (33-67 yrs) were enrolled into the GM-CSF arm. Seven tumor responses, including two durable partial responses, were observed which led to an 18-month OS rate of 25% and mOS of 56 weeks. Detailed immunological testing was performed to identify potential correlations at baseline and after treatment between biomarkers and tumor responses. Analyses included class I and II HLA typing, modulation of plasma cytokine and chemokine responses, boosting of CMV-specific antibody and IFN-g ELISPOT responses, and modulation of CMV-specific CD4 Tem cells, of which only differential trafficking of the CD4 Tem cells appears to distinguish patients with tumor responses from those with tumor progression. Single cell, RNAseq is underway in an attempt to understand mechanistic differences in these immune cell populations in Tumor Responders vs. Non-Responders. The U.S. FDA granted Fast Track Designation to VBI-1901 adjuvanted with GM-CSF in first-recurrent GBM patients, and an expansion of the ongoing trial with this formulation in this patient population, with the addition of randomization with a contemporaneous control arm, is anticipated to begin in Q3 2022.